Zrinyi Peter- a hosteremtes irodalmi modelljei es strategiai - Blažević, Zrinka (Array, 2007)
Drawing upon Murray Edelman concept of the "political spectacle", this paper is aimed at analysing diverse strategies and models of heroization in the literary discourse on the example of the cultic figures of the Croatian national imagery: Nikola Šubić Zrinski, his great-grandsons Nikola and Petar and his brother-in-law Fran Krsto Frankopan. While the first part of this paper is aimed at the investigation of discoursive construction and representation of Nikola Zrinski, the second is focused on the equal procedures evident in the process of discoursive heroization of Croatian Banus Petar and his brother-in-law Frankopan, especially in the context of their anti-Habsburg conspiracy. Detecting the contradiction and ambivalence as the most prominent features of the complex discursive and performative structure of the political spectacle within which construction and inscenation of the ethical and political habitus of the exemplary national heroes are taking place, this interpretative analysis seeks to highlight both symbolic inscriptions and ideological and political usages and functions of the "Zrinski-Frankopan complex" in diverse literary genres from the middle of the 17th to the beginning of the 21st century.